SCIENTIFIC ANALYSIS OF THE BURNISHING PROCESS FOR IMPROVING THE SURFACE QUALITY OF SMALL-DIAMETER HOLES - Oqyu'lova Nigora Inobidin's daughter (Modern American Journals, 2025)
This study focuses on the burnishing process applied to internal metallic components, specifically examining its effectiveness in improving the surface quality of small-diameter holes. Particular attention is given to the reduction of roughness, surface hardness control, and strengthening of the surface layer. The application of the burnishing method in manufacturing is scientifically justified in terms of energy efficiency, reduced processing time, and improved production productivity.
Keywords: Burnishing, surface quality improvement, small-diameter holes, deformation processes, mechanical engineering. Burnishing, Surface finishing, Plastic deformation, Residual stresses, Surface roughness.